Stochastic structural and reliability based optimization of tuned mass damper. (August 2015) - Mrabet, E.; Guedri, M.; Ichchou, M.N.; Ghanmi, S.
Abstract: The purpose of the current work is to present and discuss a technique for optimizing the parameters of a vibration absorber in the presence of uncertain bounded structural parameters. The technique used in the optimization is an interval extension based on a Taylor expansion of the objective function. The technique permits the transformation of the problem, initially non-deterministic, into two independents deterministic sub-problems. Two optimization strategies are considered: the Stochastic Structural Optimization (SSO) and the Reliability Based Optimization (RBO). It has been demonstrated through two different structures that the technique is valid for the SSO problem, even for high levels of uncertainties and it is less suitable for the RBO problem, especially when considering high levels of uncertainties. Highlights: The validity of the Taylor expansion based interval extension method is discussed. Optimum designs of TMD using the SSO and the RBO strategies are used. Numerical examples are presented to highlight the method. It has been proven that the presented method is valid with the SSO problem. The presented method is less appropriate for the RBO problem.